ANALISA MINAT BELI KONSUMEN MUSLIM TERHADAP PRODUK MAKANAN BERLABEL HALAL DI KOTA BATAM - Kelvin Kelvin; Listia Nurjanah (Program Sarjana Manajemen Universitas Internasional Batam, 2022)
Researcher conducted this research to find out whether the halal label or halal certification affected the buying interest of Muslim communities in Batam. The independent variables in the research were Subjective Norm and Religiosity. The mediating variable in the research conducted was Attitude. Meanwhile, the dependent variable in this study was the Purchase Intention. The samples in this research were Muslim communities in the city of Batam who often consumed halal food. The data of this research were 389 samples. However, 123 data did not qualify, and 266 data could be proceeded by researcher. This research was conducted with a testing process using the Smart PLS application. After conducting this research, the result showed that Religiosity had a positive effect on Purchase Intention, Subjective Norm had a positive effect on Purchase Intention, Attitude had a positive effect as a mediating variable Subjective Norm and Purchase Intention, Attitude had a positive effect as a mediating variable Religiosity and Purchase Intention.